Review: application and challenge IN Internet of Things (IoT) - jebuer, Tuka kareem (International Journal of Psychosocial Rehabilitation, 2020)
IoT is one type of the systems that explain the future vision of how to connect physical components and infrastructure where it consists of connecting a set of mechanical and digital machines or computer devices and can use wireless sensor networks with this technology, where it provides the ability to collect data and These systems allow instant access to information anywhere in the world quickly, efficiently, productively and less expensive, the main purpose in this paper its discusses this modern technology and applications used in it and areas of future application and discussed Briefly.